6(x-1)-5=4x+2(-3+x)

Simple and best practice solution for 6(x-1)-5=4x+2(-3+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-1)-5=4x+2(-3+x) equation:


Simplifying
6(x + -1) + -5 = 4x + 2(-3 + x)

Reorder the terms:
6(-1 + x) + -5 = 4x + 2(-3 + x)
(-1 * 6 + x * 6) + -5 = 4x + 2(-3 + x)
(-6 + 6x) + -5 = 4x + 2(-3 + x)

Reorder the terms:
-6 + -5 + 6x = 4x + 2(-3 + x)

Combine like terms: -6 + -5 = -11
-11 + 6x = 4x + 2(-3 + x)
-11 + 6x = 4x + (-3 * 2 + x * 2)
-11 + 6x = 4x + (-6 + 2x)

Reorder the terms:
-11 + 6x = -6 + 4x + 2x

Combine like terms: 4x + 2x = 6x
-11 + 6x = -6 + 6x

Add '-6x' to each side of the equation.
-11 + 6x + -6x = -6 + 6x + -6x

Combine like terms: 6x + -6x = 0
-11 + 0 = -6 + 6x + -6x
-11 = -6 + 6x + -6x

Combine like terms: 6x + -6x = 0
-11 = -6 + 0
-11 = -6

Solving
-11 = -6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 55-(2c+3)=4c(c+6)+c | | 7y+9=30 | | 7x-5=5(x+11)+2x-10 | | -2(m+2)=-8 | | (4x^8+11x^6-7x^2+3)-(9x^8-5x^4+8x^2-4)=0 | | 0.009(x+200)+0.06x=63 | | f(x)=10xfor | | 9c-6c=-8+11 | | 5x+6x-40=100-9x | | 45-4x*5=80 | | 8x+48=9x | | 0.5x+0.7x=1.7 | | -8=3-2(c-4)+3 | | 8+20x=x-4 | | P=50h+200 | | 100x=1000findx | | 2x+21+90=80 | | 4x*5=125 | | 45x+75z=339 | | 3x+2(4x+7)=113 | | 17x^2-17=0 | | 21+6x=23+7x | | -3w+2=14 | | 25000x-5y=0 | | X+1.23=65.6 | | 15y-1=103 | | 9x-38=4x+23 | | 11-(x-2)=3 | | 4x+6=9x+1 | | 3x+3(5x-15)=63 | | 8+c=0 | | 8=c-12 |

Equations solver categories